Bariatric surgery and diabetes: Implications of type 1 versus insulin‐requiring type 2. (22nd January 2015) - Maraka, Spyridoula; Kudva, Yogish C.; Kellogg, Todd A.; Collazo‐Clavell, Maria L.; Mundi, Manpreet S.
<x xml:space="preserve">Abstract</x> Objective To report the impact of bariatric surgery on metabolic outcomes in patients with type 1 diabetes (DM1) versus insulin‐requiring type 2 diabetes mellitus (IRDM2). Methods Ten subjects with DM1 were compared with 118 subjects with IRDM2 at baseline and at 1 and 2 years post‐bariatric surgery for: anthropometric measures, HbA1c, and number of medications (anti‐hyperglycemic, anti‐hypertensive, lipid‐lowering). Results DM1 and IRDM2 groups lost similar amounts of weight 2 years post‐bariatric surgery (39.5 ± 14.7 kg vs. 40.3 ± 24.4 kg). IRDM2 subjects had significant improvements in HbA1c (7.8% ± 1.4% vs. 6.8% ± 1.4%, P value <0.0001) and decreases in number of anti‐hyperglycemic (2.4 ± 0.8 vs. 0.7 ± 0.8, P value <0.0001), anti‐hypertensive (2.2 ± 1.3 vs. 1.3 ± 1.2, P value <0.0001), and lipid‐lowering (1.1 ± 0.8 vs. 0.6 ± 0.6, P value <0.0001) medications. DM1 subjects had no improvement in HbA1c (8.2% ± 1.6% vs. 7.8% ± 0.9%) or use of anti‐hypertensive medications (2.1 ± 1.4 vs. 2.3 ± 1.5). Their use of lipid‐lowering medications improved (1.0 ± 0.5 vs. 0.5 ± 0.8, P value 0.04). Conclusions Our study suggests that improved glycemic control may not be an expected outcome when considering bariatric surgery in patients with DM1; however, additional investigation is warranted.